Coronary artery air embolism complicating a CT-guided percutaneous lung biopsy - Deshmukh, Ashwin; Kadavani, Nirav; Kakkar, Ritu; Desai, Shrinivas; Bhat, Ganapathi M (Indian Journal of Radiology and Imaging, 2019)
Coronary arterial air embolism is an extremely rare but readily recognizable condition on computed tomography (CT) that may complicate a lung biopsy. We present an incidence of symptomatic air embolism into the right coronary artery during a percutaneous CT-guided lung biopsy that was successfully recognized during the procedure and managed accordingly. An active search for this complication should be made when the patient deteriorates on table and the usual complications (pneumothorax, vasovagal shock, etc.) are ruled out, as immediate resuscitative measures could be life-saving.
Keywords: Air embolism; coronary artery; interventional radiology; lung biopsy; thoracic imaging